Mechanical feedback coordinates cell wall expansion and assembly in yeast mating morphogenesis - Banavar, Samhita P.; Gomez, Carlos; Trogdon, Michael; Petzold, Linda R.; Yi, Tau-Mu; Campàs, Otger (PLOS Computational Biology, 2018)
Author summary All morphogenesis processes, whether at the cell scale or tissue level, require the coordination of growth and mechanics to properly shape functional structures. However, the mechanisms that coordinate these two processes in the sculpting of individual cells, and especially in walled cells, remain unknown. Using yeast mating projection growth as a model system, we show that a genetically-encoded mechanical feedback relays information about the mechanical state of the cell wall to the intracellular processes assembling it, thereby coordinating cell wall expansion and growth during cell morphogenesis. We find that mechanical feedback is essential to stabilize cell growth, but the shape and size of the cell are insensitive to the feedback and independently controlled.